Some Applications of the Reproducing Kernel Method (RKM) and the Group Preserving Scheme (GPS) - İnç, Mustafa; Akgul, Ali (Amer Inst Physics, 2017)
[Abstract Not Available]
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 19-25, 2016 -- Rhodes, GREECE